Relationship between some anthropometric indices with dynamic and static balance in sedentary female college students - Elahe Moeın; Farzaneh Movaseghı (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to evaluate the relationship between some anthropometric characteristics with dynamic and static balance in sedentary female college students. This study was carried out on a sample of 158 Iranian sedentary female college students, aged 18-25 years, during 2013-2014. Participants were selected from volunteers of Chabahar University. Anthropometric indices (body height, weight, lower-extremity lengths and widest perimeter, body mass index, waist-hip ratio) and balance (dynamic and static) were measured. Static balance with open eyes and eyes closed measured with Angel Balance Test on a stable surface and dynamic balance was evaluated by timed up and go test (TUG). Pearson correlation coefficients were used in analysis. There was a weak negative correlation between dynamic balance and lower leg length (r= -0.164) and weak positive correlation between dynamic balance and body mass index (r=0.164). In the eye open condition, static balance was related to lower leg length (r=0.172) with dominant leg. In the eye open condition with non-dominant leg and eye closed conditions there was no correlation between static balance and any anthropometric indices. The levels of significance are not high but warrant attention. It seems that there was no single anthropometric index that explained the variations in body balance among healthy sedentary young female and other factors such as the sense of sight, vestibular and proprioceptive systems have a role in the balance.